Pengaruh Citra Merek Dan Promosi Terhadap Keputusan Pembelian Sabun Wajah Poise Pada Mahasiswi UHN Medan - Gultom, Anathasya Brace Br; Sihombing, Natalia E.; Pasaribu, Vera A.R. (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2024)
This study aims to determine the effect of brand image and promotion on purchasing decisions of female students of HKBP Nommensen University. This study was conducted using a quantitative method. Data collection techniques using questionnaires. Based on hypothesis testing with the t test, the t-count value for the brand image variable is 4.307 where the value is> from t table 1.985 and the significant value for the brand image variable is 0.000 <from the significance level of 0.05 (5%). So it can be concluded that brand image has a positive and significant effect on purchasing decisions for Poise brand facial soap. And the f test obtained an f-count value of 45.760 where this value is> from the f table of 3.09. Along with the significant value is 0.000 <from the significance level of 0.05. So it can be concluded that simultaneously brand image and promotion together have a positive and significant effect on purchasing decisions for Poise brand facial soap.